Red Carrot Cells Cultured in vitro Are Effective, Stable, and Safe Ingredients for Skin Care, Nutraceutical, and Food Applications - Bianconi, Martino; Ceriotti, Laura; Cuzzocrea, Salvatore; Esposito, Emanuela; Pressi, Giovanna; Sgaravatti, Elena; Bertaiola, Oriana; Guarnerio, Chiara; Barbieri, Elisa; Semenzato, Alessandra; Negri, Stefano; Commisso, Mauro; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Plant biomasses growing in bioreactor could be developed as production systems for cosmetic ingredients, nutraceuticals and food additives. We previously reported that the red carrot cell line R4G accumulates high levels of anthocyanins, which are potent antioxidants with multiple health-promoting properties. To investigate the industrial potential of this cell line in detail, we tested extract for antioxidant and anti-inflammatory activity in the mouse monocyte/macrophage cell-line J774A.1 and in reconstructed skin tissue models. We also compared the R4G extract to commercial carrot extracts in terms of stability and metabolomic profiles. We found that the R4G extract have potent antioxidant and anti-inflammatory activities, protecting mammalian cells from the oxidative stress triggered by exposure to bacterial lipopolysaccharides and H2O2. The extract also inhibited the nuclear translocation of NF-κB in an epidermal skin model, and induced the expression of VEGF A to promote the microcirculation in a dermal microtissue model. The anthocyanins extracted from R4G cells were significantly more stable than those found in natural red carrot extracts. Finally, we showed that R4G extract has similar metabolomic profile of natural extracts by using a combination of targeted and untargeted metabolomics analysis, demonstrating the safety of R4G carrot cells for applications in the nutraceutical and food/feed industries.